Il ruolo degli IDE nella globalizzazione dell'economia - J.H. DUNNING (Moneta e Credito, 2013)
Economic globalisation has magnified the effect of fixed direct investment on growth and labor allocation. The phenomenon, which involves the interrelationship among economic events in trading economies, benefits most from foreign investment when barriers to trade exist. Furthermore, in cases where no such barriers exist, investment enhanced trade. The complementary and supportive relationship between trade and investment is most evident in the activities of multinational enterprises.